2021
DOI: 10.3390/microorganisms9020334
|View full text |Cite
|
Sign up to set email alerts
|

Do Blood Eosinophils Predict in-Hospital Mortality or Severity of Disease in SARS-CoV-2 Infection? A Retrospective Multicenter Study

Abstract: Introduction: Healthcare systems worldwide have been battling the ongoing COVID-19 pandemic. Eosinophils are multifunctional leukocytes implicated in the pathogenesis of several inflammatory processes including viral infections. We focus our study on the prognostic value of eosinopenia as a marker of disease severity and mortality in COVID-19 patients. Methods: Between 1 March and 30 April 2020, we conducted a multicenter and retrospective study on a cohort of COVID-19 patients (moderate or severe disease) who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…This study tends to show that eosinophils count< 10/mm3 was associated with mortality: OR (95% CI) 3.54 (1.23-11.4) after adjustment for age, gender, and disability (i.e., ADL < 3) older patients suffering from COVID-19. At rst glance, these results seem to be in line with literature (29)(30)(31)(32)(33) where low eosinophil count is associated with poorer prognostic and conversely, a better prognosis when subjects present eosinophilia due to asthma (34,35).…”
Section: Discussionsupporting
confidence: 89%
“…This study tends to show that eosinophils count< 10/mm3 was associated with mortality: OR (95% CI) 3.54 (1.23-11.4) after adjustment for age, gender, and disability (i.e., ADL < 3) older patients suffering from COVID-19. At rst glance, these results seem to be in line with literature (29)(30)(31)(32)(33) where low eosinophil count is associated with poorer prognostic and conversely, a better prognosis when subjects present eosinophilia due to asthma (34,35).…”
Section: Discussionsupporting
confidence: 89%
“…This conclusion correlates well with the observation that eosinophils do not play a protective or exacerbating role during SARS-CoV-2 infection [ 19 ]. In addition, it is eosinopenia that is very common and often pronounced in cases of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“… 25 On the contrary, a retrospective study included 1035 confirmed COVID-19 patients, one quarter of them were severe cases, reported that eosinopenia was not a useful predictor of mortality. 26 The studies mentioned above focused on the prognostic indication function of eosinophil levels in patients with COVID-19, but whether eosinophil accumulation in the respiratory system or overall elevation in the human body increases COVID-19 virus resistance has not yet been clarified. An urgent question is also whether the eosinophil level could alter the course of COVID-19 or whether it has only an accompanying role during the infection process.…”
Section: Discussionmentioning
confidence: 99%